Special populations: The referee and assistant referee - Reilly, T.; Gregson, W. (Journal of Sports Sciences, 2006)
The referee has responsibility for control of players' behaviour during competitive football and implementing the rules of the game. To do this, the referee and the two assistant referees are obliged to keep up with play. Referees cover 10,000 m on average during a game, mean heart rate is about 160 - 165 beats · min-1 and oxygen uptake is close to 80% of maximum (&Vdot;O2max). Assistant referees cover approximately 7500 m, mean heart rate is about 140 beats · min-1 and the corresponding oxygen uptake is 65% &Vdot;O2max. Both groups display evidence of fatigue towards the end of the game, a phenomenon that has not been thoroughly examined for nutritional interventions. The estimated energy expenditure of referees during a game exceeds 5600 kJ. Both referees and assistant referees execute unorthodox patterns of movement during match-play that increase energy expenditure over normal locomotion. As high standards of fitness and decision making are expected of professional referees, there are nutritional consequences associated with the training regimes they adopt. The effects of nutritional interventions on cognitive performance during the later stages of a game are in need of further investigation.